Does religious fasting affect energy and macro-nutrients intakes? - Khattak, Muhammad Muzaffar Ali Khan; Mamat, Nik Mazlan; Mohd Abu Bakar, Wan Azdie; Shaharuddin, Mohd Firdaus Nazri (Emerald Group Publishing Limited, 2013)
Purpose – This study was designed with the aim of assessing the energy and nutrient intakes of male university students before and during Ramadan and comparing it with the Recommended Nutrient Intake (RNI) of Malaysia.